Sex‐ and strain‐specific effects of mitochondrial uncoupling on age‐related metabolic diseases in high‐fat diet‐fed mice. Issue 2 (28th January 2022) - Goedeke, Leigh; Murt, Kelsey N.; Di Francesco, Andrea; Camporez, João Paulo; Nasiri, Ali R.; Wang, Yongliang; Zhang, Xian‐Man; Cline, Gary W.; de Cabo, Rafael; Shulman, Gerald I.
Abstract: Mild uncoupling of oxidative phosphorylation is an intrinsic property of all mitochondria and may have evolved to protect cells against the production of damaging reactive oxygen species. Therefore, compounds that enhance mitochondrial uncoupling are potentially attractive anti‐aging therapies; however, chronic ingestion is associated with a number of unwanted side effects. We have previously developed a controlled‐release mitochondrial protonophore (CRMP) that is functionally liver‐directed and promotes oxidation of hepatic triglycerides by causing a subtle sustained increase in hepatic mitochondrial inefficiency. Here, we sought to leverage the higher therapeutic index of CRMP to test whether mild mitochondrial uncoupling in a liver‐directed fashion could reduce oxidative damage and improve age‐related metabolic disease and lifespan in diet‐induced obese mice. Oral administration of CRMP (20 mg/[kg‐day] × 4 weeks) reduced hepatic lipid content, protein kinase C epsilon activation, and hepatic insulin resistance in aged (74‐week‐old) high‐fat diet (HFD)‐fed C57BL/6J male mice, independently of changes in body weight, whole‐body energy expenditure, food intake, or markers of hepatic mitochondrial biogenesis. CRMP treatment was also associated with a significant reduction in hepatic lipid peroxidation, protein carbonylation, and inflammation. Importantly, long‐term (49 weeks) hepatic mitochondrial uncoupling initiated late in life (94–104 weeks), in conjugation with HFD feeding, protected mice against neoplastic disorders, including hepatocellular carcinoma (HCC), in a strain and sex‐specific manner. Taken together, these studies illustrate the complex variation of aging and provide important proof‐of‐concept data to support further studies investigating the use of liver‐directed mitochondrial uncouplers to promote healthy aging in humans. Abstract : Here, we demonstrate that mild mitochondrial uncoupling via CRMP treatment reduces hepatic steatosis and improves hepatic insulin sensitivity in aged HFD‐fed mice. Long‐term CRMP treatment protects aged HFD‐fed mice against hepatocellular carcinoma in a strain and sex‐specific manner. Together, these studies illustrate the complex variation of aging and provide important proof of concept data to support further studies investigating the use of mitochondrial uncoupling agents to promote healthy aging in humans.